2013
DOI: 10.1016/j.electacta.2012.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of ZrTi alloys for biomedical applications

Abstract: The electrochemical behaviour of three ZrTi alloys (Zr5Ti, Zr25Ti and Zr45Ti) in Ringer's solution has been investigated. Their resistance against localized corrosion has been determined from cyclic potentiodynamic polarization (CCP) and electrochemical impedance spectroscopy (EIS) measurements, whereas scanning electrochemical microscopy (SECM) was applied to investigate the local reactivity of the passive films developed on the materials, and scanning electron microscopy (SEM) was employed to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 44 publications
5
59
1
Order By: Relevance
“…Localized corrosion can be very harmful and it is known that zirconium is susceptible to localized corrosion induced by chloride ions . However it was reported that the addition of Ti to Zr reduces the susceptibility of the localized corrosion . Transition metal/oxide interfaces have been attracted because they are used in many applications .…”
Section: Introductionmentioning
confidence: 99%
“…Localized corrosion can be very harmful and it is known that zirconium is susceptible to localized corrosion induced by chloride ions . However it was reported that the addition of Ti to Zr reduces the susceptibility of the localized corrosion . Transition metal/oxide interfaces have been attracted because they are used in many applications .…”
Section: Introductionmentioning
confidence: 99%
“…7(c). This type of EC has been widely used for valve metals, including Ti, Nb, Ta and Zr, as reported in previous work [28,[30][31][32], and it has been established based on Macdonald's Point Defect Model [33]. This model provides a picture of the formation of oxide films in terms of the generation and transport of cation and anion vacancies in a constant electric field.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 98%
“…In 1965, pure titanium implants were used clinically and long-term cases were studied, allowing the effects of implants to be tracked and observed. [5][6][7][8] It is osseointegration that leads to the success of implantation. Nowadays, titanium (Ti) is most widely used in clinical oral implants; nevertheless, the mechanical/ tensile strength of cpTi is deficient.…”
Section: Introductionmentioning
confidence: 99%